Assessing the reliability of medicinal Dendrobium sequences in GenBank for botanical species identification - Hoi-Yan Wu (Nature Portfolio, 2021)
Abstract DNA-based method is a promising tool in species identification and is widely used in various fields. DNA barcoding method has already been included in different pharmacopoeias for identification of medicinal materials or botanicals. Accuracy and validity of DNA-based methods rely on the accuracy and taxonomic reliability of the DNA sequences in the database to be compared against. Here we evaluated the annotation quality and taxonomic reliability of selected barcode loci (rbcL, matK, psbA-trnH, trnL-trnF and ITS) of 41 medicinal Dendrobium species downloaded from GenBank. Annotations of most accessions are incomplete. Only 53.06% of the 2041 accessions downloaded contain a reference to a voucher specimen. Only 31.60% and 4.8% of the entries are annotated with country of origin and collector or assessor, respectively. Taxonomic reliability of the sequences was evaluated by a Megablast search based on similarity to sequences submitted by other research groups. A small number of sequences (211, 7.14%) was regarded as highly doubted. Moreover, 10 out of 60 complete chloroplast genomes contain highly doubted sequences. Our findings suggest that sequences of GenBank should be used with caution for species-level identification. The scientific community should provide more important information regarding identity and traceability of the sample when they deposit sequences to public databases.